Monosomic Alien Addition Lines of Rice: Production, Morphology, Cytology, and Breeding Behavior - Jena, K.K.; Khush, Gurdev S. (Canadian Science Publishing, 1989)
Interspecific hybrids between three breeding lines of Oryza sativa (2n = 24 = AA) and 18 accessions of O. officinalis (2n = 24 = CC) were obtained through an embryo-rescue technique. The crossability ranged from 1.0 to 2.3%. The AC hybrids showed a low amount of chromosome pairing (0–4 bivalents) and were completely male sterile. The BC1 progeny, obtained upon backcrossing to O. sativa were allotriploid (AAC) and were also male sterile. Further backcrosses to O. sativa produced 94 BC2 plants with chromosome numbers of 2n to 2n + 6. Monosomic alien addition lines (AA + 1C) corresponding to the 12 chromosomes of the haploid complement of O. officinalis were isolated from among forty 2n + 1 BC2 plants. These addition lines differ from their diploid sibs by an array of morphological features and resemble the 12 primary trisomics of O. sativa. The female transmission rates of alien chromosomes varied from 6.6 to 26.8%. Four of the 12 monosomic alien addition lines transmitted the alien chromosome through the male gametes.Key words: chromosome pairing, introgression, embryo rescue, allotriploid, genes for insect resistance, interspecific gene transfer.